Into the ice : the story of Arctic exploration [book review] - Clement, Cinda (1999)
Curlee, Lynn. Into the Ice. Illustrated by Lynn Curlee. Houghton Mifflin, 1998. ISBN 0-395-83013-3. $16.00. 37 pp. B 3-8 NF PB Reviewed by Cinda Clement This book traces the history of Arctic exploration. It goes through the experiences several exploring expeditions have as they encounter the difficulties of this new frontier. The pictures in the book are full-page, brilliant, stark, and as startling as the Arctic itself, but the text reads like an encyclopedia. It is too bad these great illustrations couldn’t have more captivating dialogue to tell the stories, which are interesting and important. The dialogue is educational, containing good information on the expeditions and the Arctic, but it reads like a textbook, which might put off potential young readers. 40 p. : col. ill., col. map 26 cm. Children's Book and Play Review, January / February 1999